AB1037 CANAKINUMAB FOR TREATMENT OF ADULT ONSET STILL'S DISEASE-RESULTS OF THE 24 WEEKS TREATMENT AND BEYOND: A MULTI-CENTRE, PLACEBO-CONTROLLED STUDY (CONSIDER). (13th June 2020) - Kedor, C.; Listing, J.; Zernicke, J.; Weiß, A.; Behrens, F.; Blank, N.; Henes, J.; Kekow, J.; Rubbert-Roth, A.; Schulze-Koops, H.; Seipelt, E.; Specker, C.; et al.
Abstract : Background: Inhibition of interleukin-1 (IL-1) represents a promising treatment option in adult-onset Still's disease (AOSD). Canakinumab is approved for treatment of systemic juvenile idiopathic arthritis and has a marked impact on systemic as well as articular activity of the disease. Objectives: To investigate the efficacy and safety of canakinumab in patients with AOSD and active joint involvement by means of a multi-centre, double-blinded, randomized, placebo controlled trial over a period of 24 weeks with the option of a long-term extension. Methods: Patients with AOSD and active joint involvement (tender and swollen joint count ≥4 each) were stratified by pre-treatment status with biologic DMARDs to canakinumab (4 mg/kg, maximum 300 mg s.c. q4w) or placebo. After approval of canakinumab for AOSD by the European Medicines Agency, recruitment was stopped prematurely with enrollment of 35 out of 68 planned patients. The primary endpoint was the proportion of patients with a clinically-relevant reduction in disease activity at week 12 as determined by the change in disease activity score (ΔDAS28 >1.2). Results: At enrollment, patients had high active disease with a mean DAS28(ESR) of 5.4 in the canakinumab group (n=18, [CI 43.1; 85.2]) and 5·3 in the placebo group (n=17, [CI 20.1; 65.0]). In the intention-to-treat analysis, 12 (67%) canakinumab and 7 (41%) placebo patients fulfilled the primary outcome criterion (p=0.18). Figure 2 shows the DAS28-ESR disease activity by treatment groups and visits with imputation. In the per-protocol analysis, significantly higher ACR30 (61% vs. 33% p=0.033), ACR50 (50% vs. 6.7% p= 0.009) and ACR70 (28% vs. 0% p=0.049) response rates were observed in the canakinumab group compared with placebo (Figure 1 ). Two patients in the canakinumab group experienced an SAE. Conclusion: Although the study was terminated prematurely and the primary endpoint was not achieved, treatment with canakinumab led to an improvement of several outcome measures in AOSD. The overall safety findings were consistent with the known profile of canakinumab. Thus, our data support indication for IL-1 inhibition with canakinumab in AOSD. References: [1]Nirmala N et al. Gene-expression analysis of AOSD and SJIA is consistent with a continuum of a single disease entity. Pediatr Rheumatol Online J. 2015 P-values are shown above each pair of bars; P-values in red are significant ACR, American College of Rheumatology; CRP, C-reactive protein; DAS, disease activity score; EULAR, European League Against Rheumatism; PP, per-protocol Disclosure of Interests: Claudia Kedor Consultant of: Advisory Board for Novartis Pharma GmbH, Joachim Listing: None declared, Jan Zernicke: None declared, Anja Weiß: None declared, Frank Behrens Grant/research support from: Abbvie, Pfizer, Roche, Chugai, Janssen, Consultant of: Abbvie, Pfizer, Roche, Chugai, UCB, BMS, Celgene, MSD, Novartis, Biotest, Janssen, Genzyme, Lilly; Boehringer; Sandoz, Speakers bureau: Abbvie, Pfizer, Roche, Chugai, UCB, BMS, Celgene, MSD, Novartis, Biotest, Janssen, Genzyme, Lilly; Boehringer; Sandoz, Norbert Blank Grant/research support from: Novartis, Sobi, Consultant of: Novartis, Sobi, Lilly, Pfizer, Abbvie, BMS, MSD, Actelion, UCB, Boehringer-Ingelheim, Roche, Jörg Henes Grant/research support from: Novartis, Roche-Chugai, Consultant of: Novartis, Roche, Celgene, Pfizer, Abbvie, Sanofi, Boehringer-Ingelheim, , Jörn Kekow Speakers bureau: BMS, MSD, Pfizer, Roche, Andrea Rubbert-Roth Consultant of: Abbvie, BMS, Chugai, Pfizer, Roche, Janssen, Lilly, Sanofi, Amgen, Novartis, Hendrik Schulze-Koops Grant/research support from: Pfizer Inc, Eva Seipelt: None declared, Christof Specker Consultant of: Abbvie, Boehringer Ingelheim, Chugai, Lilly, Novartis, Sobi, UCB, Celgene, Janssen-Cilag, MSD, Pfizer, Roche, UCB, Toshiba, Eugen Feist Consultant of: Novartis, Roche, Sobi, Lilly, Pfizer, Abbvie, BMS, MSD, Sanofi, Speakers bureau: Novartis, Roche, Sobi, Lilly, Pfizer, Abbvie, BMS, MSD, Sanofi